Pengaruh Konsep Park and Ride pada Manajemen Lalu Lintas di Kawasan Terminal Bubulak Bogor - Prasetyo, Rizky; Murtejo, Tedy; Alimuddin, Alimuddin; Sudrajat, Endang (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
Bogor City is an area located in West Java Province, Indonesia. This area is located 50 km south of Jakarta and 120 km southwest of Bandung City. With an annual population growth rate of ± 1.53 percent, the population of Bogor City in 2020 is ± 1,081,009 according to the Bogor City Central Statistics Agency (BPS). The city of Bogor has an area of 118.5 square kilometers. This research was conducted to determine the feasibility level of the Park and Ride development plan in Bogor City, especially at Bubulak Terminal. Traffic counting and identification surveys were carried out on main roads which were then processed using Microsoft Excel to determine parking accumulation and determine fluctuations in motorbikes and cars. Next, the interview data was processed to determine the number of people's interest in the development of Park and Ride based on gender, age, trip duration, purpose of trip, parking duration, monthly fuel expenditure, desire for parking rates and those who agreed to use Park and Ride at the time the survey was conducted. At 06.00-21.00 WIB on the road in the Bubulak Terminal area. From the results of data processing using Microsoft Excel, it was found that the characteristics of Park and Ride facility users and also the number of requests for Park and Ride facility users for motorbikes was 2349, while for cars it was 272 with a planned lifespan of up to 2021, this proves the need for increased interest in construction of Park and Ride at Bubulak Terminal, Bogor City. Keywords: Park and Ride, Bubulak Bus Station, Urban Transportation.